Covert Surveillance in the Structural Elements of the Criminally-Remedial Averment - AMIRKHANOV, Bakhytzhan K. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
This study is aimed at the determination of the structure of the criminally-remedial averment, the content of its elements and the place of the covert surveillance in them. On the basis of the classification of the scientific positions, the comparison and collation of the scientific achievements were conducted with a view to their critical evaluation and achievement of the own results. The formal-logical method of interpretation of the criminal procedure law and the comparative-legal method were used in the study. The subject of study is considered in process, using the principle of the unity of analysis and synthesis. As a result of the study, the structure of the criminally-remedial averment, the content of its elements and the place of the covert surveillance in them were determined. These results allowed to develop the practical recommendations for the improvement of the criminal procedure law and the mechanism of the averment procedure through the covert surveillance.
Keywords: criminal proceeding; averment; cognition; covert surveillance; operational-investigative activity